In‐Situ AFM Study of Zinc Electrodeposition in a Deep Eutectic Solvent - Ting Wang; Xintao Xu; Kaixuan Li; Yuteng Fan; Hao Yan; Feng Zhu; Jianzhang Zhou; Jiawei Yan; Bingwei Mao (ChemElectroChem)
Abstract Zinc‐based batteries are promising for applications in large‐scale energy storage and other scenarios due to their high voltage, large theoretical capacity, and abundant reserves. Compared to traditional aqueous electrolytes, deep eutectic solvents (DESs) offer advantages such as wide electrochemical window, good stability, and fewer parasitic reactions. They can effectively regulate the growth morphology of zinc deposits and suppress dendrite formation during zinc deposition/stripping processes. However, there is currently a lack of direct observation for underlying mechanisms of zinc deposition/stripping processes in DESs. In this study, combined with electrochemical methods, in‐situ atomic force microscopy (in‐situ AFM) has been utilized to investigate the deposition behavior of zinc metal from ZnCl2 precursor in a deep eutectic solvent composed of choline chloride and ethylene glycol (ethaline). Cyclic voltammetric measurements indicate that zinc deposition is a kinetically controlled process. And in‐situ AFM reveals the hexagonal morphology and layered deposition of zinc on highly oriented pyrolytic graphite (HOPG). Our observations benefit the understanding of the kinetics of zinc deposition/stripping in deep eutectic solvent ethaline at a microscopic level.